Developing Sukawati Village Temple as a Heritage Tourism Attraction in Bali - I Putu Aditya Prawira Putra; I Nyoman Subagia; I Gusti Made Widya Sena (Institut Pariwisata dan Bisnis Internasional, 2026)
Sukawati Village Temple has great potential as a heritage tourism while maintaining traditional philosophical values and sustainable management. This study aims to evaluate the development of tourist attractions as cultural heritage tourist destinations based on Tri Hita Karana. Using a qualitative approach, data was collected through in-depth interviews with 12 key informants, including indigenous leaders and local officials, as well as field observations. The findings of the study show that Sukawati Village Temple not only functions as a cultural heritage, but also as a center for various social, economic, and cultural activities. This research contributes to the cultural heritage tourism literature by operationalizing the values of Tri Hita Karana into a practical community-based tourism management model. The results show that community-led governance is very important to maintain authenticity while improving the visitor experience. This research advances the application of a spiritual philosophical framework in managing sustainable cultural heritage sites.